Implementing pedagogical translanguaging in trilingual schools. (August 2020) - Cenoz, Jasone; Santos, Alaitz
Abstract: This article reports on a study of primary and secondary school teachers in Basque schools where Basque, Spanish and English are included in the curriculum. Traditionally, the three languages have been taught separately and the possible benefits of using the whole linguistic repertoire to establish links between the languages had not been acknowledged. New trends in multilingual education focusing on the whole linguistic repertoire and translanguaging have provided opportunities to change traditional approaches to teaching and to explore the potential advantages of translanguaging. In this study, a group of teachers from different trilingual schools were provided with theoretical and practical information about translanguaging and were asked to implement pedagogical translanguaging in their own class. Teachers were given a guideline for the implementation and were asked to prepare a lesson plan including activities that involved the use of two or more languages for pedagogical purposes. Then, the teachers taking part in this study used translanguaging for at least one lesson, received feedback from their students and reflected on the implementation. The results of this study show that pedagogical translanguaging can provide new opportunities for language learning and language awareness in the context of multilingual education.